New methodology for sustainable development towards sustainable transportation system - Burinskienė, Marija (Technological and Economic Development of Economy, 2009)
“New methodology for sustainable development towards sustainable transportation system” Technological and Economic Development of Economy, 15(1), p. 5–9. First published online: 21 Oct 2010